PELUANGA KERJA ALUMNI IAIN (Perspektif Sosiologis) - Syarif, Jamal (State Institute of Islamic Studies (IAIN) Palu, 2012)
Educational institutions/schools considered in addition to teaching the knowledge and skills also contribute effectively instill modern values is required as a prerequisite for any nation that was about to enter the era of industrialization. Schools are also considered as one of the important socialization tool (in addition to the family and community) that the ruling class always engineered to preserve the existing social structure. Schools were seen as a market culture (culture market), in which social factors are simultaneously trying to achieve certain goals or exchanged for something, such as a diploma, prestige, control over certain social class, and other social qualifications .Kata Kunci: Â Lapangan pekerjaan, fakultas, alumni, dan status sosial